Drug–drug interaction profile of components of a fixed combination of netupitant and palonosetron: Review of clinical data. (June 2016) - Natale, James J; Spinelli, Tulla; Calcagnile, Selma; Lanzarotti, Corinna; Rossi, Giorgia; Cox, David; Kashef, Kimia
Neurokinin-1 (NK1 ) receptor antagonists (RAs) are commonly coadministered with serotonin (5-HT3 ) RAs (e.g. palonosetron (PALO)) to prevent chemotherapy-induced nausea/vomiting. Netupitant/palonosetron (NEPA), an oral fixed combination of netupitant (NETU)—a new NK1 RA—and PALO, is currently under development. In vitro data suggest that NETU inhibits CYP3A4 and is a substrate for and weak inhibitor of P-glycoprotein (P-gp). This review evaluates potential drug–drug interactions between NETU or NEPA and CYP3A4 substrates/inducers/inhibitors or P-gp substrates in healthy subjects. Pharmacokinetic (PK) parameters were evaluated for each drug when NETU was coadministered with PALO (single doses) and when single doses of NETU or NEPA were coadministered with CYP3A4 substrates (erythromycin (ERY), midazolam (MID), dexamethasone (DEX), or oral contraceptives), inhibitors (ketoconazole (KETO)), or inducers (rifampicin (RIF)), or a P-gp substrate (digoxin (DIG)). Results showed no relevant PK interactions between NETU and PALO. Coadministration of NETU increased MID and ERY exposure and significantly increased DEX exposure in a dose-dependent manner; NETU exposure was unaffected. NEPA coadministration had no clinically significant effect on oral contraception, although levonorgestrel exposure increased. NETU exposure increased after coadministration of NEPA with KETO and decreased after coadministration with RIF; PALO exposure was unaffected. NETU coadministration did not influence DIG exposure. In conclusion, there were no clinically relevant interactions between NETU and PALO, or NEPA and oral contraceptives (based on levonorgestrel and ethinylestradiol exposure). Coadministration of NETU or NEPA with CYP3A4 inducers/inhibitors/substrates should be done with caution. Dose reduction is recommended for DEX. Dose adjustments are not needed for NETU coadministration with P-gp substrates.